The Use of Real-Time Quantitative PCR to Detect Circulating Prostate-Specific Membrane Antigen mRNA in Patients with Prostate Carcinoma - CHU, DA-CHANG; CHUANG, CHENG-KENG; LIOU, YI-FANG; TZOU, RON-DAR; LEE, HSIAO-CHUN; SUN, CHIEN-FENG (Annals of the New York Academy of Sciences, 2004)
: Prostate‐specific antigen (PSA) has long been criticized for its lack of specificity in screening for the occurrence of prostate cancer. In this study, we tried to measure levels of another biomarker, prostate‐specific membrane antigen (PSM), in the peripheral circulation from subjects with either prostate cancer or benign prostatic hyperplasia (BPH). Total RNA was extracted from blood samples of 70 patients with prostate cancer and 19 with BPH. Reverse transcription was performed to convert mRNA to cDNA. The cDNA was analyzed with a novel real‐time quantitative polymerase chain reaction (PCR) protocol to measure PSM mRNA levels in the circulation. Melting curve analysis was adapted to assure that correct amplification data were obtained. Results showed that 41 of 70 prostate cancer patients had positive results, whereas 9 of 19 BPH cases were negative. Therefore, the sensitivity and specificity were determined to be 58.6% and 47.4%, respectively. For comparison, traditional nested PCR was performed to investigate whether the new method was superior. The sensitivity and specificity of nested PCR were determined to be 27.1% and 57.9%, respectively. The detection limits of these two methods were 0.0005 ng (for the real‐time quantitative PCR method) and 0.5 ng of PSM‐cDNA (for the nested PCR method). In conclusion, we have successfully developed a novel, noninvasive real‐time quantitative PCR method to detect the PSM mRNA levels in the peripheral circulation of prostate cancer subjects. This method may provide references for urologists diagnosing prostate cancer or monitoring the patient's condition after treatment.